2022
DOI: 10.1002/adma.202110115
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Scale Auxetic Hierarchical Mechanical Metamaterials for Shape Morphing

Abstract: years, it has been possible to note an emergence of promising directions of studies that address the possibility of observing these effects. In fact, one of the most interesting directions of studies related to this topic are mechanical metamaterials, [3,[28][29][30][31][32] that is, structures that can exhibit counterintuitive mechanical behavior based primarily on their design. Mechanical metamaterials are known for their ability to exhibit counterintuitive mechanical properties such as auxetic behavior, [33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 70 publications
0
49
0
Order By: Relevance
“…More specifically, if one was to construct the structure composed of multiple unit-cells corresponding to a different deformation pattern, then in general, it would be possible to arbitrarily modify the shape of the entire structure. If the mismatch in the Poisson's ratio between different parts of the system would be significant, it would be possible to observe considerable shape-morphing similarly to the concept proposed in [66] (in the aforementioned study, it was demonstrated that an initial shape of the metamaterial subjected to the mechanical deformation can be significantly modified depending on the ratio in the Poisson's ratio associated with different parts of the structure). The possibility of exhibiting controllable shape-morphing could be used in the design of stents in order to better support specific parts of the blood vessel that are particularly weak.…”
Section: Vibrational Propertiesmentioning
confidence: 75%
See 1 more Smart Citation
“…More specifically, if one was to construct the structure composed of multiple unit-cells corresponding to a different deformation pattern, then in general, it would be possible to arbitrarily modify the shape of the entire structure. If the mismatch in the Poisson's ratio between different parts of the system would be significant, it would be possible to observe considerable shape-morphing similarly to the concept proposed in [66] (in the aforementioned study, it was demonstrated that an initial shape of the metamaterial subjected to the mechanical deformation can be significantly modified depending on the ratio in the Poisson's ratio associated with different parts of the structure). The possibility of exhibiting controllable shape-morphing could be used in the design of stents in order to better support specific parts of the blood vessel that are particularly weak.…”
Section: Vibrational Propertiesmentioning
confidence: 75%
“…Hierarchical mechanical metamaterials [59,60,61,62,63,64,65,66] are a class of structures composed of multiple structural levels having their own geometry that typically can deform irrespective of each other. This, in some cases, allows the system to exhibit quantitatively very different mechanical properties without the need of being reconstructed.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, with the development of micromachining, constructing hierarchical auxetic honeycombs at the micro-scale has received extensive attention [55,56]. Although the concept of the RCW honeycomb proposed in this manuscript is confirmed by the conventional 3D printing process, its further manufacturing and research at the microscale, such as by the microprinting technology, is still of significance.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the huge prospect in many applications such as medical equipment and flexible electronics, it is considered to be one of the most promising directions in this field [51][52][53][54]. Dudek et al [55] developed and fabricated 2D and 3D hierarchical mechanical metamaterials at the microscale by the 3D microprinted polymers, and found that the proposed designs have great capability of shape morphing. Cho et al [56] proposed a novel strategy to construct multilevel hierarchical metamaterials with programmable geometric shapes by the fractal cutting strategy, and confirmed it at both the macroscale and microscale.…”
Section: Introductionmentioning
confidence: 99%
“…A few extensive studies have been performed on different polymers to obtain the printable properties as a function of printing parameters, via Raman scattering or other characterisation techniques [14,15]. However, from one setup to another and for different reasons, characterisation must be repeated and adapted each time.…”
Section: Introductionmentioning
confidence: 99%